The role of stage in teacher training for early childhood education: a debate, the University of Florence and the University of Vale do Itajaí models - Claudete Bonfanti; Clara Maria Silva; Luciane Maria Schlindwein (Firenze University Press, 2016)
The paper discusses the stage role in teacher training for early childhood education. Are research subjects the trainees of the Faculty of Education at the University of Vale do Itajaí (Brazil) in 2014, and Corso di Laurea in Scienze della Formazione Primaria indirizzo Scuola dell'infanzia dell'Università di Firenze (Italy) in 2015. The study is guided in qualitative research (Bogdan & Biklen, 1994). Interviews and documents of both courses were analyzed. We seek to support the theoretical studies (Bondioli & Ferrari, 2008; Calvani, 2014; Catarsi, 2014; Catarsi & Fortunati, 2012; Gomes, 2009; Pimenta & Lima, 2012; Silva, 2014). The analysis indicates that sometimes the students do not understand the connection between theory and practice, referring to the internship in the child education. It is considered that overcoming the dichotomy between theory and practice constitutes weakness to be overcome in the initial training of future teachers. We did not intend to compare the two contexts, but this paper is a suggestion for future researchers to continue the debate on the weaknesses identified in this research. O papel do estágio na formação de professores para a educação infantil: em debate, o modelo da Università degli Studi di Firenze e o da Universidade do Vale do Itajaí O trabalho discute o papel do estágio na formação dos professores para a educação infantil. São sujeitos da pesquisa as estagiárias do curso de Pedagogia da Universidade do Vale do Itajaí (Brasil), em 2014, e do Corso di Laurea in Scienze della Formazione Primaria indirizzo Scuola dell'infanzia dell'Università di Firenze (Italia), em 2015. O estudo pauta-se na abordagem qualitativa de pesquisa (Bogdan & Biklen, 1994) e foram analisados entrevistas e documentos de ambos os cursos. Buscou-se respaldo nos estudos teóricos de (Bondioli & Ferrari, 2008; Calvani, 2014; Catarsi, 2014; Catarsi & Fortunati, 2012; Gomes, 2009; Pimenta & Lima, 2012; Silva, 2014). A análise indica que não é sempre que as estudantes compreendem a conexão entre teoria e prática, ao se tratar do estágio em educação infantil. Considera-se que a superação da dicotomia entre teoria e prática se constitui em fragilidade a ser superada na formação dos futuros professores. Não tivemos a intenção de comparar os dois contextos, todavia fica a sugestão para futuros pesquisadores de continuar o debate em torno das fragilidades apontadas na presente pesquisa.